CD1d-independent NK1.1+ Treg cells are IL2-inducible Foxp3+ T cells co-expressing immunosuppressive and cytotoxic molecules - Park, Hyun Jung; Lee, Sung Won; Park, Yun Hoo; Kim, Tae-Cheol; Van Kaer, Luc; Hong, Seokmann (Frontiers in Immunology, 2022)
Regulatory T cells (Treg) play pivotal roles in maintaining self-tolerance and preventing immunological diseases such as allergy and autoimmunity through their immunosuppressive properties. Although Treg cells are heterogeneous populations with distinct suppressive functions, expression of natural killer (NK) cell receptors (NKR) by these cells remains incompletely explored. Here we identified that a small population of Foxp3+CD4+ Treg cells in mice expresses the NK1.1 NKR. Furthermore, we found that rare NK1.1+ subpopulations among CD4+ Treg cells develop normally in the spleen but not the thymus through CD1d-independent pathways. Compared with NK1.1- conventional Treg cells, these NK1.1+ Treg cells express elevated Treg cell phenotypic hallmarks, pro-inflammatory cytokines, and NK cell-related cytolytic mediators. Our results suggest that NK1.1+ Treg cells are phenotypically hybrid cells sharing functional properties of both NK and Treg cells. Interestingly, NK1.1+ Treg cells preferentially expanded in response to recombinant IL2 stimulation in vitro, consistent with their increased IL2Rαβ expression. Moreover, DO11.10 T cell receptor transgenic NK1.1+ Treg cells were expanded in an ovalbumin antigen-specific manner. In the context of lipopolysaccharide-induced systemic inflammation, NK1.1+ Treg cells downregulated immunosuppressive molecules but upregulated TNFα production, indicating their plastic adaptation towards a more pro-inflammatory rather than regulatory phenotype. Collectively, we propose that NK1.1+ Treg cells might play a unique role in controlling inflammatory immune responses such as infection and autoimmunity.